Age-specific and sex-specific incidence of systemic lupus erythematosus: an estimate from cross-sectional claims data of 2.3 million people in the German statutory health insurance 2002. Issue 1 (25th November 2016) - Brinks, Ralph; Hoyer, Annika; Weber, Sergej; Fischer-Betz, Rebecca; Sander, Oliver; Richter, Jutta G; Chehab, Gamal; Schneider, Matthias
Abstract : Objective: To provide an estimate of age-specific incidence rate of physician-diagnosed systemic lupus erythematosus (SLE) for German men and women. Methods: The age-specific and sex-specific prevalence of diagnosed SLE in claims data is used to estimate the incidence in the German male and female population. The claims data set stems from a representative sample of the statutory health insurance in 2002 and comprises 2.3 million people. The statutory health insurance covers >85% of the German population. Results: The estimated incidence rates are 0.9 (95% CI 0.7 to 1.1) per 100 000 person-years for men and 1.9 (95% CI 1.7 to 2.2) per 100 000 person-years for women. The age-specific incidence rate of SLE in the male population has a maximum of 2.2 (95% CI 1.0 to 3.4) per 100 000 person-years at the age of 65–70 years. In women, the incidence is peaking at the rate of 3.6 (95% CI 2.9 to 4.3) cases per 100 000 person-years at the age of 20–25 years, but has a second local maximum (2.6, 95% CI 1.5 to 3.8) at menopausal age. Conclusions: For the first time, representative data on the incidence of SLE in Germany are provided. The estimated incidence rates of SLE for men and women in Germany are at the lower end of other estimates from comparable European countries.